Liquid argon time projection chamber calibration using cosmogenic muons, and measurement of neutrino induced charged kaon production in argon in the charged current mode (MicroBooNE experiment) - Meddage, Varuna Crishan N (Kansas State University, 2019)
The MicroBooNE experiment at Fermilab uses the novel LArTPC technology to reconstruct neutrino interactions with liquid argon. The experiment consists of a detector having an active mass of 85 tons of liquid argon, where the operational electric field of the TPC is 0.273 kV/cm. While BNB neutrino beam at Fermilab is the main source for neutrinos for the experiment having an average energy of ~0.8 GeV, the NUMI neutrino beam at Fermilab also provides high energy neutrinos to perform different physics analyses. The MicroBooNE experiment has been in operation since october 2015. Its major physics goals include investigating into the anomalous production of electron neutrino like events as observed by MiniBooNE and LSND experiments and detail studies of neutrino-argon cross sections at lower neutrino energies. Moreover, the experiment will also serve as R&D for future LArTPC experiments like the already proposed SBN and DUNE programs. One of the major operational requirements of any LArTPC experiment including MicroBooNE is to achieve a high liquid argon purity keeping the electronegative contaminants like H2O and O2 at low concentration levels. This dissertation first describes how to perform an electron attenuation measurement using cosmogenic muons, which provides a handle over the the amount of electronegative impurities inside our detector medium. Likewise this measurement also serves as the first step towards reconstruction of particle energies as MicroBooNE must compensate for the loss of ionization electrons due to capture by electronegative contaminants. Secondly, the discussion is about how to calibrate any LArTPC detector in removing any spatial and temporal variations of the dQ/dx (charge deposited per unit length) spectrum using cosmogenic muons and then how to calculate correct energies of particle interactions with these calibrated out dQ/dx values. The translation of dQ/dx to particle energies (dE/dx - energy deposited per unit length) makes use of the stopping muons coming from neutrino interactions as the standard candle. The final discussion is about the neutrino induced charged kaon production at charged current mode in the lower neutrino energies of MicroBooNE experiment. This measurement is crucial as there is no such measurement so far on argon at the scale of neutrino energies used for MicroBooNE while already existing measurements on lighter nuclear targets are also sparse. This dissertation presents the first identified neutrino induced kaon candidates in MicroBooNE.
Keywords: MicroBooNE; Kaon production; Detector calibration